Guardians of Detroit : Architectural Sculpture in the Motor City - Morrison, Jeffrey (Book collections on Project MUSE., 2019)
Detroit is home to amazing architectural sculpture?a host of gargoyles, grotesques, and other silent guardians that watch over the city from high above its streets and sidewalks, often unnoticed or ignored by the people passing below. Jeff Morrison?s 'Guardians of Detroit: Architectural Sculpture in the Motor City' documents these incredible features in a city that began as a small frontier fort and quickly grew to become a major metropolis and industrial titan.0Detroit developed steadily following its founding in 1701. From 1850 to 1930 it experienced unprecedented population growth, increasing from 21,019 to over 1,500,000 people. A city of giants, Detroit became home to people of towering ambition and vision who gained wealth and sought to leave their mark on the city they loved. This aspiration created a massive building boom during a time when architectural styles favored detailed ornamentation, resulting in a collection of architectural sculpture unmatched by any other U.S. city. 'Guardians of Detroit' is a first-of-its-kind project to explore, document, and explain this singular collection on a building-by-building basis and to discover and share the stories of these structures and the artists, artisans, and architects who created them.